2007
DOI: 10.1007/s00011-007-6100-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rectal administration of rebamipide on dextran sulfate sodium-induced colitis: Role of hepatocyte growth factor

Abstract: Rectal administration of rebamipide is effective for DSS-induced colitis in association with induction of HGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Rebamipide has been reported that it has a superior efficacy to the rat colitis model induced by dextran sulfate, 18,19) although rebamipide did not have a clinical application to IBD yet.…”
Section: -17)mentioning
confidence: 99%
“…Rebamipide has been reported that it has a superior efficacy to the rat colitis model induced by dextran sulfate, 18,19) although rebamipide did not have a clinical application to IBD yet.…”
Section: -17)mentioning
confidence: 99%
“…On days 3,5,7,9,11,13, and 15 after the third gene transfer in the UC rats that were used to detect HGF expression, the colonic tissues treated with TPH were removed, and the paraffinembedded sections were analyzed for the HGF expression by immunohistochemistry. For HGF, the sections were treated with anti-human HGF monoclonal antibodies (R&D Systems, Minneapolis, MN, USA) followed by a treatment with peroxidaseconjugated goat anti-mouse immunoglobulins (Jackson ImmunoResearch Laboratories, West Grove, PA, USA).…”
Section: Exogenous Protein Expression In Colonic Tissuementioning
confidence: 99%
“…[4][5][6][7][8] Among them, hepatocyte growth factor (HGF) plays multiple roles in enhancing colonic epithelium proliferation, inhibiting cell apoptosis, 9,10 reducing inflammatory infiltration, alleviating symptoms and mucosal lesions, 5,11 and improving local angiogenesis. [4][5][6][7][8] Among them, hepatocyte growth factor (HGF) plays multiple roles in enhancing colonic epithelium proliferation, inhibiting cell apoptosis, 9,10 reducing inflammatory infiltration, alleviating symptoms and mucosal lesions, 5,11 and improving local angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation